Aflatoxin B1 and ochratoxin A in imported and Lebanese wheat and -products. Issue 3 (3rd July 2021) - Daou, Rouaa; Joubrane, Karine; Khabbaz, Lydia Rabbaa; Maroun, Richard G.; Ismail, Ali; El Khoury, André
ABSTRACT: AFB1 and OTA are produced in food products due to climatic conditions like temperature and humidity. In Lebanon, few studies address AFB1 and OTA contamination in wheat and wheat products. In this study, a total of 312 samples of wheat and wheat products were collected from different sites, including port, silos, mills, and supermarkets were analysed. Wheat and wheat products consumption in Lebanon was quantified using a food frequency questionnaire. Exposure to AFB1 and OTA was calculated and liver and kidney cancer risk were evaluated. Results showed that AFB1 and OTA were, respectively, found in 65.7% and 100% of the samples, with 0.6% and 17.6% exceeding the maximum limit set by the European Commission. AFB1 was shown to be associated with 0.076 additional cancer cases per 100, 000 persons per year and OTA weekly exposure was shown to be 53.2 ng/kg bw, which is less than the Provisional Tolerable Weekly Intake of 100 ng/kg bw.